1999
DOI: 10.1111/j.1468-1331.1999.tb00014.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurological characteristics of HIV‐infected men and women seeking primary medical care

Abstract: We examined the neurological differences between human immunodeficiency virus (HIV)-infected men (n = 193) and women (n = 41) receiving primary medical care. There was no difference between men and women in the rate of HIV-related neurological syndromes (i.e. polyneuropathy, myelopathy, myopathy, HIV- dementia [HAD]). A logistic regression analysis indicated that low CD4+ cell count predicted all neurological syndromes. In addition, HAD was predicted by intravenous-drug use and lower education level, while neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 13 publications
1
9
1
Order By: Relevance
“…Even so, cognitive impairment may also result from white matter atrophy (and associated cortical atrophy) which occurs in parallel with HIV-induced depletion of CD4 + cells (the rate of these two processes may not be connected, but both are caused by HIV). The CD4 + T-cell number reflects patients' neurological status (Lopez et al, 1999;, submitted for publication-b). White matter loss was greater in patients with CD4 + counts less than 200 cells/µl-relative to those with better immune function and CD4 + counts around 500 cells/µl (Stout et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Even so, cognitive impairment may also result from white matter atrophy (and associated cortical atrophy) which occurs in parallel with HIV-induced depletion of CD4 + cells (the rate of these two processes may not be connected, but both are caused by HIV). The CD4 + T-cell number reflects patients' neurological status (Lopez et al, 1999;, submitted for publication-b). White matter loss was greater in patients with CD4 + counts less than 200 cells/µl-relative to those with better immune function and CD4 + counts around 500 cells/µl (Stout et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a small study of 49 HIV-1-seropositive women living in Puerto Rico found that rates of cognitive impairment (77.6%), asymptomatic cognitive impairment (32.7%), minor cognitive motor disorders (16.3%), and HIV-associated dementia (28.6%) were similar to rates found among men in the United States, Europe, and Australia (Wojna et al 2006). It has been posited that earlier reports of a vulnerability to HIV-related dementia among women may reflect the lower education and higher proportion of injection drug use among HIV+ women than men and access to antiretroviral therapy (Lopez et al 1999). …”
Section: Neurological Function In Hiv+ Women Versus Menmentioning
confidence: 99%
“…Relative to men, women living with HIV are more likely to reside in marginalized settings, be less educated, and have a greater frequency of substance use including intravenous drug use (IDU) [34][37]. Further, compared to HIV+ men, HIV+ women are less likely to receive recommended health care.…”
Section: Introductionmentioning
confidence: 99%